Detecção de fungos em sementes, inoculação em sementes, identificação de raças e controle químico de drechslera tritici-repentis em trigo - Bertagnolli, Victória Vieira (2015)
Tan spot of wheat is one of the main diseases in southern Brazil, accounting for losses and significant crop damage. Considering the importance of the disease, the objectives of this work were: i) identify and quantify the fungi associated to wheat seeds, ii) determine the best conditions for artificial inoculation Drechslera tritici-repentis in wheat seeds, iii) identify the races of the fungus D.tritici-repentis isolated from leaves and wheat seeds collected in Rio Grande do Sul and Paraná and iv) verify the efficacy of fungicides for the control of wheat yellow spot. The experiments were carried out in the laboratory, growth chambers and in field experimental area. Seven genera of fungi were identified in wheat regions of Cultivation and Use Value (CUV) I (cold / wet / high) and II (moderately hot / wet / low), being these Alternaria, Aspergillus, Bipolaris, Drechslera, Fusarium, Penicillium and Stagonospora. Drechslera was the economically important known pathogen more present in wheat seeds in RS. The CUV I region showed a higher incidence of Bipolaris and Fusarium compared to CUV II region. Regarding inoculation of the fungus in seeds, the water potential of -0.6 MPa under 24 hours inoculation time favored the fungus infection in wheat seeds without harming the germination and seedling emergence. In the race identification experiment were found races 1, 2, 4 and 7 of the fungus, and the race 4 has been found at higher frequency (56.25%), followed by race 2 (18.75%), 7 (18.75%), and 1 (6,25%). This is the first report of the presence of races 4 and 7 in Brazil. During the 2013 season, adding propiconazole to the trifloxystrobin + prothioconazole mixture provided the greatest control efficiency. Regarding the wheat crop in 2014, the addition of protectant fungicides (mancozeb or iprodione) to the mixture (triazole + strobilurin) was able to raise the control efficacy to more than 70%. All fungicide treatments were statistically higher than the control for yield, but not different from one another